Efektivitas Pemberian Olahan Jantung Pisang Sebagai Nutrition-Based Complementary Therapy Pendamping Multiple Micronutrient Supplementation terhadap Perubahan Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia: Studi Quasi-Eksperimental - Dyah Ayu Septika Wijaya; Reny Retnaningsih; Tut Rayani Akhoshini Wijayanti; Ani Khoirinda (Jurnal Abdimas Jatibara, 2026)
Introduction: Anemia during pregnancy affects 32.3% of women globally and 27.7% in Indonesia, significantly increasing risks of maternal hemorrhage and neonatal complications. While Multiple Micronutrient Supplementation (MMS) is the standard intervention, its effectiveness is often hampered by low iron bioavailability and gastrointestinal side effects such as constipation. Banana blossom (Musa paradisiaca) contains high iron (up to 56.4 mg/100g) and natural Vitamin C as a cofactor, offering a synergistic approach to optimize iron absorption.Objectives: This study aims to evaluate the effectiveness of banana blossom as a nutrition-based complementary therapy alongside MMS on hemoglobin (Hb) changes and clinical symptom improvement among anemic pregnant women.Methods: A quasi-experimental study with a pretest-posttest control group design was conducted on 50 pregnant women in their II and III trimesters at Praktek Mandiri Bidan Sumidjah Ipung, Malang. Subjects were divided into an intervention group (MMS + 100g sautéed banana blossom/day) and a control group (MMS only) for 14 days. Hb levels were measured using EasyTouch GCHb, while clinical symptoms (fatigue, dizziness, shortness of breath) were assessed via a structured Likert scale (0–10).Results: The intervention group showed a substantial mean Hb increase of 1.35 g/dL (9.81 ± 0.65 to 11.16 ± 0.58 g/dL), successfully raising the average status above the WHO anemia threshold (>11 g/dL). In contrast, the control group only showed an increase of 0.44 g/dL (9.89 ± 0.72 to 10.33 ± 0.68 g/dL). Statistical analysis confirmed a significant difference between groups (p < 0.001). Furthermore, the intervention group reported a more progressive reduction in clinical symptom scores (5.0 points) compared to the control group (2.0 points). Notably, the intervention group experienced zero reports of constipation, compared to 16% in the control group, attributed to the high dietary fiber content (52–54%) of banana blossom.Conclusions: Integrating banana blossom as a nutrition-based complementary therapy significantly accelerates hemoglobin recovery and alleviates clinical symptoms in anemic pregnant women when paired with MMS.